Physico-Chemical Studies on Some Mixed Ligand Hydrido-phosphine Complexes of Ir(III) with Ethylene Thiourea - Pandey, R.N.; Kant Kumar, Shashi; Kumar, Sanjay; Kumar Singh, Sanjoy (Asian Journal of Chemistry, 2012)
Some mixed ligand hydrido-phosphine complexes of Ir(III) with ethylene thiourea have been prepared and investigated using various physico-chemical techniques. Ethylene thiourea forms stable coloured complexes depending on the conditions of the reaction. The systematic shift in the four thioamide bands of ethylene thiourea in the IR spectra indicate its bonding through thiocarbonyl sulphur. The ligand field bands of complexes are obscured by charge transfer band in the electronic spectra. Tentative octahedral configuration of all complexes have been assigned.